Fracture Risk After Gastric Bypass Surgery: A Retrospective Cohort Study. (13th August 2018) - Axelsson, Kristian F; Werling, Malin; Eliasson, Björn; Szabo, Eva; Näslund, Ingmar; Wedel, Hans; Lundh, Dan; Lorentzon, Mattias
ABSTRACT: Gastric bypass surgery constitutes the most common and effective bariatric surgery to treat obesity. Gastric bypass leads to bone loss, but fracture risk following surgery has been insufficiently studied. Furthermore, the association between gastric bypass and fracture risk has not been studied in patients with diabetes, which is a risk factor for fracture and affected by surgery. In this retrospective cohort study using Swedish national databases, 38, 971 obese patients undergoing gastric bypass were identified, 7758 with diabetes and 31, 213 without. An equal amount of well‐balanced controls were identified through multivariable 1:1 propensity score matching. The risk of fracture and fall injury was investigated using Cox proportional hazards and flexible parameter models. Fracture risk according to weight loss and degree of calcium and vitamin D supplementation 1‐year postsurgery was investigated. During a median follow‐up time of 3.1 (interquartile range [IQR], 1.7 to 4.6) years, gastric bypass was associated with increased risk of any fracture, in patients with and without diabetes using a multivariable Cox model (hazard ratio [HR] 1.26; 95% CI, 1.05 to 1.53; and HR 1.32; 95% CI, 1.18 to 1.47; respectively). Using flexible parameter models, the fracture risk appeared to increase with time. The risk of fall injury without fracture was also increased after gastric bypass. Larger weight loss or poor calcium and vitamin D supplementation after surgery were not associated with increased fracture risk. In conclusion, gastric bypass surgery is associated with an increased fracture risk, which appears to be increasing with time and not associated with degree of weight loss or calcium and vitamin D supplementation following surgery. An increased risk of fall injury was seen after surgery, which could contribute to the increased fracture risk. © 2018 American Society for Bone and Mineral Research.